Household Income Dynamics in Rural China - Jalan, Jyotsna; Ravallion, Martin (World Bank, Washington, DC, 2014)
Theoretical work has shown that nonlinear dynamics in household incomes can yield poverty traps and distribution-dependent growth. If this is true, the potential implications for policy are dramatic: effective social protection from transient poverty would be an investment with lasting benefits, and pro-poor redistribution would promote aggregate economic growth. The authors test for nonlinearity in the dynamics of household incomes and expenditures using panel data for 6,000 households over six years in rural southwest China. While they find evidence of nonlinearity in the income and expenditure dynamics, there is no sign of a dynamic poverty trap. The authors argue that existing private and social arrangements in this setting protect vulnerable households from the risk of destitution. However, their findings imply that the speed of recovery from an income shock is appreciably slower for the poor than for others. They also find that current inequality reduces future growth in mean incomes, though the "growth cost" of inequality appears to be small. The maximum contribution of inequality is estimated to be 4-7 percent of mean income and 2 percent of mean consumption.